(untitled) (Research, Society and Development, 2022)
Corynebacterium pseudotuberculosis is the etiologic agent of caseous lymphadenitis (CL), a chronic infectious disease that affects sheep and goats. Numerous serological tests have been developed to detect the disease, being the Enzyme Immunoassay (ELISA) one of the most used due to its advantages of sensitivity and specificity. The present study aimed to evaluate the reactivity of a panel of Corynebacterium pseudotuberculosis antigens in goats experimentally infected with non-forming and biofilm-forming strains. Eighteen Canindé goats were used: group 1 - negative control animals, group 2 - goats infected with non-biofilm-forming bacteria and group 3 - goats infected with a biofilm-forming strain. Recombinant antigens CP40 and PLD, membrane fraction antigens (F3) and C. pseudotuberculosis secreted antigens (BHI) were tested. The sensitivity and specificity of the indirect ELISA tests for all antigens were 100%. However, the optical density (OD) values recorded in the BHI ELISA were lower than those found in the other ELISA tests, suggesting that specific antigens may have better sensitivity and specificity in the diagnosis of CL.